UPAYA MENINGKATKAN KEMAMPUAN BAHASA ANAK MELALUI METODE BERCERITA PADA ANAK KELOMPOK B TK TULIP PELAIHARI - Rusmakiah, Rusmakiah (Jurnal Analisis Pendidikan Sosial, 2024)
The existence of a kindergarten learning curriculum in which there are aspects of child development such as the development of religious morals, social emotional, language, physical motor, cognitive and art, then in learning activities one of the aspects of language development that contains indicators of development, such as storytelling and retelling. For that I discuss the problems so far by holding storytelling activities but have not met satisfactory results for teachers, children and schools. I was assisted by colleagues trying to research why it could be like what happened in the discussion above. Examining the teacher's own problems, teaching materials, tools, children and incomplete supporting materials from all the data collected, we conducted research and improvements step by step in the way of learning the storytelling method, from the first, second and third cycles and so on to meet the success of learning activities in class. Finally, from the implementation of this class action (CAR), it produces a satisfactory result of learning activities and can improve aspects of development, especially the development of the language being discussed, all objectives will be achieved as a whole.